The Social Contract: A Personal Inquiry into the Evolutinary Sources of Order and Disorder - Ardrey R.; Ardrey B. (New York Atheneum, 1970)
Violation of biological command has been the failure of social man. Vertebrates though we may be, we have ignored the law of equal opportunity since civilization s earliest hours. Sexually reproducing beings though we are, we pretend today that the law of inequality does not exist. And enlightened though we may be, while we pursue the unattainable we make impossible the realizable. In his two previous books, Robert Ardrey exploded a series of philosophical landmines. African Genesis (1961) introduced his new evolutionary approach to an understanding of men. Then came The Territorial Imperative (1966), whose title is now a common phrase in our language. The Social Contract is the third in the series, and it denies that men are created equal but that they deserve absolute equality of opportunity. Robert Ardrey maintains that since the publication of Rousseau s Social Contract two centuries ago, men have wasted social resources, converted much of education into a process of brain-washing, committed themselves to one political insane asylum after another, all in pursuit of a goal that is a natural impossibility in any sexually reproducing species. Discarding the myth, Robert Ardrey combines his wealth of knowledge of animal ways with the new insights of modern biology and the newest revelations concerning human evolution to probe perplexing contemporary problems: the revolt of the young, the status struggle and the role of leadership, population control, urban overcrowding, violence in civilized life. Praise for the 1970 edition: Robert Ardrey s The Social Contract is as imaginative and exciting as his African Genesis or The Territorial Imperative, but this new book is broader in scope, better balanced, and more philosophical than its predecessors. I disagree with some of Ardrey s opinions concerning human aggression, because I have greater faith than he has in the power of environmental conditioning. But this does not affect my conviction that The Social Contract will be of immense value in helping the public to probe into the dark and misty areas where zoology, anthropology, and prehistory join to account for the origins of man as a social animal. Rene Dubos, Rockefeller University
Keywords: 57 ioi